E-kenegaraan online exam practise - Kasim, Shahreen; Ibrahim, Siti Sarah; Wahid, Norfaradilla; Hafit, Hanayanti (Penerbit UTHM, 2017)
In the world of sophisticated technology, the use of internet is becoming the norm and no longer is something strange like a long time ago. Indirectly, the user makes the Internet as a major tool to facilitate their daily work. Various type of system are being designed and developed will be used for the purpose of facilitating and expediting for a daily work and will give a good information and beneficial to consumers. System is a set of components that work together in one environment to achieve specific objectives in which it is also a resource to save, collect, process and retrieve data by using certain procedures. To create something for their system, it is very concerned about planning and process system to produce a good and orderly system. This paper shows e-Kenegaraan Online Exam Practise which is a system that builds to enable the students to answer the questions of the subject Kenegaraan easily. The questions are taken from previous semesters. It also has a practise module where students can answer questions as an exercise. Besides, there are also some systems that are look alike same as the system to be built such system Zoom A, system Score A, system Latih Tubi, system Youth4work (Taylor, 2013), system of My English Pages (O'Brien, 2014) and system Astro Tutor TV UPSR (Vihar, 2015).